Artikel Review: Tinjauan Pemilihan Obat Antipiretik untuk Anak-Anak - Fira Aulia Fatan; Indah Laily Hilmi; Salman Salman (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
When in good physical health, humans can easily carry out various activities. However, there are times when the body cannot carry out activities as usual because the body is exposed to diseases which usually begin with symptoms that can be felt. Fever is a symptom of the onset of the disease with an increase in body temperature above normal (> 38 ° C). To overcome the fever that occurs in children, pharmacological and non-pharmacological therapy can be done. Pharmacological therapy is by giving fever-reducing drugs. Fever drugs often used are antipyretic groups, for example, paracetamol or ibuprofen. This study aims to examine what antipyretic drugs are most often chosen for the treatment of fever in children. The method in this study is a systematic review traced through Google Scholar and PubMed with a 10-year publication range from 2012 to 2022. The results of this study show that paracetamol and ibuprofen are indeed the first choices for treating fever in children. In choosing antipyretics, there is still a balance between paracetamol or ibuprofen; this is influenced by knowledge factors, ranging from information obtained through personal searches to information from relatives and from doctor's prescriptions that have been received.